Método de precificação alinhado à gestão de ponto de equilíbrio para multiprodutos em uma microempresa do ramo de confecção de fardamentos profissionais em Fortaleza/CE - Ferreira, Lara Barreira (2017)
Due to the competitive environment, companies face the obligation to provide quality products with low prices, which requires the knowledge of efficient management techniques. This scenario is unfavourable for micro and small companies to ssurvive, since they have to stand firm to face market competition, which includes more experienced medium and large companies. In addition, to meet an increasingly demanding customer, it is necessary to maintain competitive prices and quality products. There is also the need to impose prices that can cover fixed and variable expenses and guarantee profitability. In this context, the aim of the present study is to define a method of price formation along with the analysis of break-even in a microenterprise of clothing industry, specialized in uniforms, in fortaleza/ce. Regarding the methodology, this study is characterized as an applied research with an exploratory purpose and a quantitative approach. Some technical procedures have been used, such as bibliographical and documentary research and the case study. The results show that the analysis model delivered to the company is consistent with its reality and size. It is also easy to understand and apply. Therefore, the results are effective.